The Relationship between Frequency of Prayer and Death Anxiety in Cancer Patients - Negar Ranjbar Hajabadi1 , Roya Ebrahimi1 , Sakine Farhadi2 , Hojjati Hamid3 , Mahboubeh Tabrsa4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Cancer is a chronic and fatal disease. In advanced stages of cancer when patients notice their impending death, they become increasingly afraid of death. Meanwhile, having faith and resorting to prayer act as non-medical treatment and palliative care. This study aimed to investigate the relationship between praying and anxiety of death in cancer patients. Method: This descriptive- correlation study was conducted on 96 cancer patients who had been referred to the Food and Drug Administration of Golestan province in Iran to receive agonist drugs. Templar and Marioliga’s standard questionnaire was used as data collection tool. Data were analyzed by logistic regression test. Results: Pearson’s correlation test showed a significant but reverse relationship between prayer and death anxiety (P<0.2, r=-0.24), so that with increase in prayer, death anxiety reduced. Conclusion: According to chronic nature of cancer and prolong treatment that it acquires, non pharmacological methods such as religion can be effective in improving mental health and reducing anxiety of dying patients.